International banking in the new era post-crisis challenges and opportunities - Kim, Suk-Joong; McKenzie, Michael D., Prof (International finance review ;, 2010)
The latest volume of the IFR series is titled International banking in the new era: Post-crisis challenges and opportunities. The volume includes original papers that examine various issues concerning challenges and opportunities for international banks in the rapidly changing global environment. The deregulation of developed countries financial markets over the past two decades has seen an evolution of the roles performed by banks. This reshaping of the traditional boundaries of commercial and investment banking activities has served to blur the distinction between domestic and international banking activities and to some extent contributed to the current international financial crisis. In addition, the development of banking systems in emerging markets have added to the opportunities and challenges faced by multinational banks. The current financial crisis has only served to accelerate this process of change as the roles of banks are once again being redefined with the possibility of a return to a more controlled environment. Theoretical, empirical, and policy-oriented contributions address issues that are relevant to international banking in this new and rapidly changing environment.